1990
DOI: 10.1038/344774a0
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus encodes three G protein-coupled receptor homologues

Abstract: Human cytomegalovirus (HCMV) is a herpesvirus with a genome of 230 kilobases (Kb) encoding about 200 genes. Although infection is generally innocuous, HCMV causes serious congenital and neonatal disease, and is a dangerous opportunistic pathogen in immune-deficient individuals. We have identified a family of three HCMV genes which encode polypeptides containing seven putative membrane-spanning domains, and a series of well-defined motifs characteristic of the rhodopsin-like G protein-coupled receptors (GCRs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
170
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(172 citation statements)
references
References 52 publications
1
170
0
1
Order By: Relevance
“…Previously, four genes encoding vGPCRs have been identified in the HCMV genome (US27, US28, UL33, and UL78) (4). Although a recent study has suggested that the HCMV genome contains an additional 11 genes that putatively encode proteins possessing 7 transmembrane domains (5), these genes seem to lack other sequences characteristic of the family of GPCR genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, four genes encoding vGPCRs have been identified in the HCMV genome (US27, US28, UL33, and UL78) (4). Although a recent study has suggested that the HCMV genome contains an additional 11 genes that putatively encode proteins possessing 7 transmembrane domains (5), these genes seem to lack other sequences characteristic of the family of GPCR genes.…”
Section: Discussionmentioning
confidence: 99%
“…Within the HCMV genome, four genes encoding GPCRs have previously been identified (US27, US28, UL33, and UL78) (4). Recently, it has been suggested that the HCMV genome may contain additional putative GPCR genes (5).…”
mentioning
confidence: 99%
“…Sequences encoding functional GPCRs have also been found in the genome of a number of DNA viruses, including human cytomegalovirus (HCMV) (Bankier et al, 1991;Chee et al, 1990), herpes virus saimiri (HVS) (Nicholas et al, 1992) and Kaposi's sarcoma associated herpesvirus (KSHV) (Arvanitakis et al, 1997). The HCMV, which infects leukocytes, ®broblasts and epithelial cells, contains in its genome three predicted open reading frames, UL27, UL28, and UL33, encoding typical GPCRs, which are believed to represent functional chemokine receptors (Ahuja and Murphy, 1993;Neote et al, 1993).…”
Section: Oncogenic Potential Of G Protein-coupled Receptorsmentioning
confidence: 99%
“…These genes can be arranged into four groups based on sequence homology, genome location, and function of the respective gene product. One group (the US28 family) consists of two GCR genes: US27 and US28 (23). Both are exclusively present within an unconserved region of the HCMV genome (22).…”
Section: Discussionmentioning
confidence: 99%
“…The KSHV chemokine receptor was also shown to stimulate cellular proliferation (4), transformation, and angiogenesis (7). A distinctive set of chemokine-like receptors is exclusively encoded by betaherpesviruses: HCMV UL33 (23), rat cytomegalovirus (RCMV) R33 (9), murine cytomegalovirus (MCMV) M33 (54), and human herpesvirus 6 and 7 (HHV-6 and -7) U12 (33,49). Recently, we found that the RCMV R33 gene is essential for the pathogenesis of viral infection in vivo and that unlike wild-type (wt) virus, an RCMV R33 null mutant could neither enter nor replicate in salivary gland epithelial cells of infected rats (9).…”
mentioning
confidence: 99%